A gestão escolar no contexto de crise do capital: a transposição do modelo empresarial para o chão da Escola Pública na Rede Estadual no Ceará - Amâncio, Nivânia Menezes (2016)
This study aimed to examine the implementation process of the business model of management into the public school Ceará state system, based on the concepts and trends of the overall management approach, as well as their influences on the management of public schools, critically analyzing the adoption of these entrepreneurship mechanisms. Consonant with our line of research work and education, we chose a critical guiding framework of analysis of the object of study, the dialectical historical materialism. The dissertational study aimed at authors such as Marx (1998), Mészáros (2011), Harvey (1999), Antunes (2009), among others, the theoretical framework to understand the contextual factors related to socioeconomic sphere; Paro (2012), Behring (2001) and Oliveira (2002), the foundation necessary to elucidate theoretical conceptions of the school management in the capital of the times of crisis. The methodology to undertake such a study consisted of qualitative research, bibliographical and research has also made an empirical character through case study with the use of techniques such as observation and interview with the management team a school institution located in Fortaleza. From the data analysis and theoretical framework were identified as, over the years, the logic of school management tried to establish a fine line with the business logic, and in its development, advance to expedients increasingly committed to the market interests and companies, making capital of conveniences, in fact, needs of educational institutions, leading to the apparent distance of a critical educational model, emancipatory and transformative.